Investigation on Shear Buckling of Corrugated Web Beams with Reinforced Web Openings. Issue 4 (14th September 2022) - Wang, Jian; Li, Zheng; Robra, Jörgen; Pasternak, Hartmut; Euler, Mathias
Abstract: Corrugated web beams are welded I‐sections with thin‐walled sinusoidal corrugated webs and flanges made of wide flat steel that have been developed as an alternative to steel girders with flat webs. In comparison with hot‐rolled or welded I‐beams with flat webs, corrugated web beams are connected with considerable material savings and fully automated production. Assuming the same load‐bearing capacity, corrugated web beams are lighter than those with a flat web, since the corrugated web beams can often be loaded up to their plastic resistance without reinforcement of the web. The research on the load‐bearing behavior of corrugated web beams without web openings is relatively mature. However, the resistance of corrugated web beams with reinforced web openings, as they are often used in buildings for installations, has not well experimentally been investigated, yet. This paper deals with the shear resistance of corrugated web beams with reinforced square web openings. Three specimens of different geometry with two square web openings were tested. The experiments are compared with a Finite Element Analysis by Abaqus® and with an analytical model allowing simplified calculation. Both models can relatively accurately calculate the shear resistance. The experimental and numerical results show that the increase of the shear resistance of perforated corrugated web beams depends on the wall‐thickness and the steel grade of the web opening reinforcement.